Promoting post-traumatic growth in cancer patients: a randomized controlled trial of guided written disclosure - Cafaro, Valentina; Rabitti, Elisa; Artioli, Giovanna; Costantini, Massimo; De Vincenzo, Francesco; Franzoni, Francesca; Cavuto, Silvio; Bertelli, Tatiana; Deledda, Giuseppe; Piattelli, Angela; Cardinali, Lisa; De Padova, Silvia; et al. (Frontiers in Psychology, 2024)
Background: Cancer is a life-threatening disease that triggers not only vulnerability to distressing symptoms but also a meaning-making process that may lead to post-traumatic growth. As people often struggle to integrate cancer illness into their meaning system to reach an adaptive meaning, psychological interventions focused on a reappraisal of the illness experience can facilitate this process. This multicenter randomized controlled trial (RCT) was primarily aimed at assessing the efficacy of a writing intervention known as a guided disclosure protocol (GDP), compared to a generic writing intervention, in promoting post-traumatic growth in stage I-III breast and colon cancer patients at the end of their adjuvant chemotherapy.Between January 2016 and August 2020 recruitment of eligible subjects took place during follow-up clinical consultations. Assessment occurred at baseline (T0), after the intervention (T1, 3 months from baseline), and at 6 months from baseline (T2). Both interventions consisted of three 20minute writing sessions to be performed once every two weeks. Change in post-traumatic growth was assessed using the Posttraumatic Growth Inventory, meaning with the Constructed Meaning Scale, and psychological distress with the Impact of Event Scale and the Hospital Anxiety and Depression Scale.In the five participating centers, 102 eligible patients were randomized and 72 participants completed follow-up evaluation. Most patients were women (79.4%), had breast cancer (68.6%), and stage I (27.5%), or stage II (44.1%) disease. Mean differences did not reach statistical significance for any of the dependent variables. However, an effect of the GDP, although not statistically relevant, was observed after the intervention in terms of enhanced post-traumatic growth and increased distress measured with the Impact of Event Scale.